Corrigendum: Temporal trends of COVID-19 antibodies in vaccinated healthcare workers undergoing repeated serological sampling: an individual-level analysis within 13 months in the ORCHESTRA cohort - Collatuzzo, Giulia; De Palma, Giuseppe; Violante, Francesco S.; Porru, Stefano; Filon, Francesca Larese; Fabianova, Eleonora; Violán, Concepción; Vimercati, Luigi; Leustean, Mihaela; Rodriguez-Suarez, Marta Maria; Sansone, Emanuele; Sala, Emma; et al. (Frontiers in immunology, 2023)
[This corrects the article DOI: 10.3389/fimmu.2022.1079884.].